Effects of vertical staking and different types of manures on growth, yield and quality of strawberry (Fragaria × ananassa Duch.) (Journal of the Bangladesh Agricultural University, 2020)
Strawberry is a very popular, refreshing and nutritious fruit having powerful antioxidant and a safe, delicious addition to any diet. An experiment was conducted at the Landscaping section of the Department of Horticulture, Bangladesh Agricultural University, Mymensingh during the period from October 2018 to April 2019 to develop a sustainable technology for optimum growth, yield and quality of strawberry cv. RU-1 (Festival) through vertical farming. The experiment comprised three vertical staking viz., 1.5, 3.0 and 4.5 feet (ft) above ground staking, and five organic manures viz., control (no manures), cowdung @ 500 g/plant, mustard oilcake (MOC) @ 100 g/plant, poultry manure @ 500 g/plant and cowdung+MOC+poultry manure @ (500+100+500) g/plant. The twofactor experiment was conducted in randomised complete block design with three replications. Significant variations were observed due to vertical staking and organic manures on all the parameters studied. Highest plant height (15.95 cm), number of leaves (27.62), number of flowers (24.86), number of runner (4.73) and number of fruits per plant (22.90), fruit length (3.70 cm) and diameter (3.04 cm), individual fruit weight (13.87 g), yield per plant (318.82 g) and TSS (8.23%) were observed at 4.5 ft above ground staking and application of cowdung+MOC+poultry manure @ (500+100+500) g/plant, while the lowest plant height (9.61 cm), number of leaves (15.02), number of flowers (12.40), number of runner (2.18) and number of fruits per plant (22.90), fruit length (3.70 cm) and diameter (3.04 cm), individual fruit weight (13.87 g), yield per plant (124.48 g) and TSS (6.40%) were recorded at 1.5 ft above ground staking with control. Thus, combined treatment of 4.5 ft above ground staking with cowdung+MOC+poultry manure @ (500+100+500) g/plant was found to be better in respect of optimum growth, yield and quality of strawberry.J Bangladesh Agril Univ 18(2): 307–315, 2020https://doi.org/10.5455/JBAU.83030